Implementation of a German-Language Voice User Interface as a Pronunciation Practice Medium for Students of German Language Education in Makassar - Alamsyah; Syarifah Fatimah; Muftihaturrahmah Burhamzah; Sabrina Saiidi (Journal of Vocational, Informatics and Computer Education, 2025)
Purpose – Pronunciation acquisition remains a major challenge for Indonesian learners of German because several German phonemes are absent from the Indonesian phonological system. This study investigated the effectiveness of a German-language Voice User Interface (VUI) as a pronunciation practice medium for undergraduate students in the German Language Education programme at Universitas Negeri Makassar, Indonesia, focusing on five challenging German phonemes: /r/, /ü/, /ö/, /ch/, and /ä:/. Methods – A one-group pretest-posttest quasi-experimental design was employed with 36 undergraduate students. The VUI-based pronunciation intervention was conducted over eight weeks. Data were collected using the Pronunciation Accuracy Rating Scale (PARS), Speech Intelligibility Scores (SIS) assessed by two native-speaker judges (ICC = 0.89), a Pronunciation Confidence Questionnaire (PCQ), and a Technology Acceptance Questionnaire (TAQ). Data were analysed using the Wilcoxon Signed-Rank test (α = .05). Findings – Pronunciation performance improved significantly following the intervention. The overall mean PARS score increased from 50.5 to 72.0, with an N-Gain of 43.4% (Z = −5.241, p < .001, r = 0.87). SIS scores improved from 51.8 to 72.3 (p < .001, r = 0.84). All five PCQ dimensions showed descriptive gains, and the overall PCQ score improved significantly (p < .001, r = 0.86), with the overall confidence mean increasing from 2.64 to 4.05. Technology acceptance was high (TAQ mean = 4.23), and peer recommendation intention received the highest rating (M = 4.44). Among the target phonemes, /r/ and /ä:/ showed the highest N-Gains (45.0% and 44.9%), while /ö/ remained the most challenging (41.1%). The /ch/ phoneme had the lowest pre-test score and the largest absolute gain. Research Implications and Originality – Findings should be interpreted in light of the study’s single-group design, limited sample, short intervention period, and absence of delayed post-testing. This study is the first to evaluate a German-language VUI for pronunciation practice in a South Sulawesi higher education context and contributes an adapted PARS instrument together with evidence-based recommendations for German pronunciation pedagogy.